Prolonged APTT and autoimmune overt hypothyroidism identified postpartum: a case report - Maja Hjelm Lundgaard; Allan Carlé; Ulla Birgitte Christiansen; Anne Sørensen; Søren Risom Kristensen; Stine Linding Andersen (European Thyroid Journal, 2023)
Introduction: Thyroid disorders have been linked to abnormalities in the coagulation system, and a hypocoagulant state has been proposed in hypothyroidism. The assessment of thyroid function is, however, not routinely recommended as part of the assessment for coagulation disorders. Case presentation: We present a 32-year-old woman who had no history of thyroid disease and who recently gave birth preterm because of severe preeclampsia and intrauterine growth restriction. Due to severe placental dysfunction, she underwent a routine biochemical assessment of the coagulation system 6 months postpartum, and a prolonged activated partial thromboplastin time (APTT) (43 s) was identified along with a low level of coagulation factor VIII (0.44 IU/mL), and a low level of von Willebrand factor (vWF) antigen (0.35 IU/mL), vWF activity (0.38 IU/mL) as well as reduced generation of thrombin. The assessment of thyroid function in the patient identified autoimmune, overt hypothyroidism with a thyroid-stimulating hormone (TSH) concentration of 139 mIU/L, low levels of the peripheral thyroid hormones (total thyroxine: 43 nmol/L, total triiodothyronine: 0.9 nmol/L), and high levels of thyroid peroxidase antibodies (296 U/mL) as well as thyroglobulin antibodies (927 U/mL). Conclusion: In this case, prolonged APTT provided a diagnostic clue for the assessment of thyroid function in a young woman with a recent history of severe placental dysfunction. The identification of autoimmune, overt hypothyroidism emphasizes that measurement of TSH may be of clinical importance in cases of unexplained prolonged APTT or other biochemical signs of abnormalities in the coagulation system.